2014
DOI: 10.1016/j.rmed.2013.09.002
|View full text |Cite
|
Sign up to set email alerts
|

A cohort study of interstitial lung diseases in central Denmark

Abstract: ILD and IPF incidence was 4.1 and 1.3 per 100,000 inhabitants/year. The diagnostic re-evaluation raised the number of IPF diagnoses, but a diagnostic "grey zone" was still evident in patients with UIP features not qualifying the patients to be diagnosed with IPF. The GAP index was valuable as a measure of IPF severity in this cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
132
5
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(156 citation statements)
references
References 22 publications
14
132
5
5
Order By: Relevance
“…Although the clinical features are the same, NSIP is reported to have a better prognosis than iNSIP, [196]. The incidence of iNSIP is estimated to be 3 per million [197]. Clinically, NSIP is characterized by shortness of breath, and cough.…”
Section: Idiopathic Nonspecific Interstitial Pneumoniamentioning
confidence: 99%
“…Although the clinical features are the same, NSIP is reported to have a better prognosis than iNSIP, [196]. The incidence of iNSIP is estimated to be 3 per million [197]. Clinically, NSIP is characterized by shortness of breath, and cough.…”
Section: Idiopathic Nonspecific Interstitial Pneumoniamentioning
confidence: 99%
“…In a Danish cohort, the median duration of symptoms before first visit to a referral centre was 28 months [10]. A prospective study reported a median diagnosis delay of 26 months [11].…”
Section: Introductionmentioning
confidence: 99%
“…However, some patients experience an accelerated decline, with acute respiratory worsening and exacerbations [12,13]. It is the type of lung fibrosis with the highest mortality rate, as the median length of survival is 3–5 years [811,14], which means that IPF has a poorer prognosis than a number of malignant diseases [7,15]. In 2006, Gribbin and colleagues reported a 43% 5-year survival rate among patients with IPF, and Navaratnam later estimated a 5-year survival rate of 37% in 2011 [4,16].…”
Section: Introductionmentioning
confidence: 99%